Information Visualization to Assist in the Audit of Supply and Demand for Exams at a Cooperative of Health Care Professionals - De Camargo, Luiz Felipe [UNESP]; Cesar Estevam, Evandro; Baglie, Luiz S.S.; Quintanilha Baptista, Fabricio; Baptista, Fabricio; Brega, Jose Remo F. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
In this study, we propose the use of four visualizations techniques (trade deficit, 3D scatter plot, circle packing, and chord diagram) to better understand and analyze four important issues in cost management of a private medical work cooperative These issues have been determined during 11 interview sessions with directors and managers from said cooperative and are: monthly revenues and expenses that the cooperative has with patient care, by contract; viability of contracts; requests for examinations made by professionals licensed by the cooperative in which they are the executors; and requests for exams performed by professionals licensed by the cooperative that are executed by other professionals licensed by the cooperative The visualizations are then demonstrated with real data obtained from the database of cooperative, which are first filtered using the interquartile range test and analyzed using the violin plot technique The use of Visualization techniques aim to highlight possible problems that may occur, such as medical abuse, fraud, feasibility of contracts with companies or even medical errors that directly or indirectly influence the cost of the health organization.
Keywords: cost management; information; interquartile range test; medical; visualization